Simulated annealing approach in solving the minimax problem with fixed line barrier - Tuan Mahmud, Tuan Mariam (2013)
Minimax location model is a class of location problems in which customers need the facility especially in emergency situation. The objective of this problem is to minimize the maximum distance between facility and the existing customers. The facility can be hospital, fire station and military service. This study involves fixed line barrier where the customers need to go through the passage on the barrier in order to move from one point to another point if necessary. Examples of line barrier are rivers, lakes and mountains. The single-facility problem is solved exactly by solving the MINLP problem using LINGO. Simulated Annealing approach is used in order to solve the multi-facility problem, coded using C++ programming. The procedure of SA algorithm is provided. The results for single facility and multi-facility problems are provided.